2022
DOI: 10.5465/annals.2020.0210
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking “Ideas” in Creative Work: A Multidisciplinary Review

Abstract: New ideas are central to a wide array of organizational phenomena and research that involve creativity and innovation. Yet, there is little consensus on what the concept of 'ideas' means, with a broad range of creative outputs being conceptualized as ideas. This fragmentation makes it challenging to compare studies and build a cumulative base of knowledge. To integrate different streams of organizational research, we reviewed papers across the creativity, innovation, entrepreneurship, design, knowledge creatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 201 publications
(270 reference statements)
1
15
0
Order By: Relevance
“…Viewing ideas as closer when they move towards implementation mirrors research on temporal psychological distance, which shows that events, plans, thoughts and actions are represented in an abstract form when they are far in the future 1 , and more concrete form when they are temporally close (Trope & Lieberman, 2010). Yet, ideas can also be generated and developed through a physical form (Hua et al, 2022)-that is, by physically or materially enacting the idea by engaging with material (Stigliani & Ravassi, 2018;Sawyer & DeZutter, 2009) or an embodiment of the idea (Heracleous & Jacobs, 2008;…”
Section: Contextual Distancementioning
confidence: 99%
See 1 more Smart Citation
“…Viewing ideas as closer when they move towards implementation mirrors research on temporal psychological distance, which shows that events, plans, thoughts and actions are represented in an abstract form when they are far in the future 1 , and more concrete form when they are temporally close (Trope & Lieberman, 2010). Yet, ideas can also be generated and developed through a physical form (Hua et al, 2022)-that is, by physically or materially enacting the idea by engaging with material (Stigliani & Ravassi, 2018;Sawyer & DeZutter, 2009) or an embodiment of the idea (Heracleous & Jacobs, 2008;…”
Section: Contextual Distancementioning
confidence: 99%
“…Elaboration is defined as refining, clarifying, and checking a core idea to develop it further (Perry- Smith & Mannucci, 2017). This implies that through elaboration, ideas progress in a relatively linear way, from vague notions to more detailed and complete versions (e.g., Berg, 2019;Hua et al, 2022). Consider the example of writing a book described in the previous section.…”
Section: Generating Creative Ideasmentioning
confidence: 99%
“…Research has also found that ideas have different characteristics. They can act as mental representations that are often unelaborated and transmittable, but can also act as physical representations that are interpretable and communicable through action (Hua et al 2022). This means that ideas need to be both conceived and communicated, and ideas that are communicated by the idea creator can trigger further intellectualisation by person evaluating the idea, which can be continuous and emergent, and lead to the creation of new ideas or idea enhancements by the individual (Sosa 2019;Ulrich & Nielsen 2020;Sukhov et al 2021;Hua et al 2022).…”
Section: Ideas For Innovationmentioning
confidence: 99%
“…They can act as mental representations that are often unelaborated and transmittable, but can also act as physical representations that are interpretable and communicable through action (Hua et al 2022). This means that ideas need to be both conceived and communicated, and ideas that are communicated by the idea creator can trigger further intellectualisation by person evaluating the idea, which can be continuous and emergent, and lead to the creation of new ideas or idea enhancements by the individual (Sosa 2019;Ulrich & Nielsen 2020;Sukhov et al 2021;Hua et al 2022). This conceptualisation challenges the understanding of idea evaluation as a decision gate, and points to the importance of elaboration, interpretation, clarification, and the creation of new ideas during evaluation.…”
Section: Ideas For Innovationmentioning
confidence: 99%
See 1 more Smart Citation